Using Illustrated Envelopes as a Medium to Enhance Students' Poetry Writing Skills - Khadijah Khadijah (Akademika, 2024)
Based on the results of observations at SD Negeri 4 Banda Aceh class V, it was found that the obstacle was that students faced difficulties in writing. Therefore, the problem of students with minimal skills in writing poetry is because students lack or have difficulty in giving opinions or statements in writing poetry. The evaluation of the research for this study is how to implement illustrated envelope media to improve the poetry writing skills of class V students of SD Negeri 4 Banda Aceh? While the purpose of the study is to implement illustrated envelope media to improve the poetry writing skills of class V students of SD Negeri 4 Banda Aceh.So the research method used is the experimental method which uses media that is implemented with pre-test and post-test questions for the first group. Data collection techniques are with pre-test and post-test. In starting to implement learning using media with a pre-test after that the media implementation will be carried out before the post-test is carried out. The results of the study can be obtained with illustrated envelope media to improve the poetry writing skills of class V students of SD Negeri 4 Banda Aceh. The details of the significant t test (sig.4 tailed) are using the paired sample test formula 0.08 or 8. Therefore 0.00 <0.008 therefore the Ha acquisition is successful and Ho fails.So the acquisition of the t test value in the implementation of the illustrated envelope media is to improve the poetry writing skills of grade V students of SD Negeri 4 Banda Aceh.